Pengembangan Video Animasi Dengan Aplikasi Powtoon Pada Materi Mawaris Mata Pelajaran Fikih Di MTsN 15 Tanah Datar - Pratama, Yusuf; Maimori, Romi; Abra, Abhanda; Susrizal, Silvia (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This thesis research departs from problems seen in the field, where currently many educators still use conventional media. The background of this thesis is that the only media used by teachers in the eyes of Jurisprudence is the blackboard in the school. Even though at the school there are infocus facilities that can be used as learning media, teachers also do not utilize technology-based media. This has an impact on students' interest in learning and the quality of learning. Therefore, the researcher wants to develop an animated video on the Islamic Jurisprudence subject, using the Powtoon application at MTsN 15 Tanah Datar. The aim of this research is to determine the validity and practicality of the product being developed, namely animated videos on the Islamic Jurisprudence subject, the material on Mavaris. This research uses a type of field research, with the ADDIE (Analysis, Design, Development, Implement and Evaluation) development model method. The research procedure begins with the needs analysis stage of product development, the design or product planning stage, the product development stage, the implementation or product testing stage and the evaluation stage. Data collection tools include validation sheets and questionnaires. The product trial subjects are located at MTsN 15 Tanah Datar. Data analysis techniques for validation and response questionnaires use the Aiken Formula. Based on the results of the validity test of animated videos using the Powtoon application in Class IX at MTsN 15 Tanah Datar, the validation results on the media aspect in general are 0.94 with the criteria